1998
DOI: 10.1128/jb.180.12.3031-3038.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Developmentally Regulatedalb1Gene ofAspergillus fumigatus: Its Role in Modulation of Conidial Morphology and Virulence

Abstract: Aspergillus fumigatus, an important opportunistic pathogen which commonly affects neutropenic patients, produces conidia with a bluish-green color. We identified a gene, alb1, which is required for conidial pigmentation. The alb1 gene encodes a putative polyketide synthase, and disruption ofalb1 resulted in an albino conidial phenotype. Expression of alb1 is developmentally regulated, and the 7-kb transcript is detected only during the conidiation stage. Thealb1 mutation was found to block 1,3,6,8-tetrahydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
166
0
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(186 citation statements)
references
References 67 publications
(76 reference statements)
13
166
0
3
Order By: Relevance
“…It is also possible, although less likely, that other MedA-dependent factors are responsible for mediating the reduced virulence of this strain. Conidia of the DmedA mutant displayed alterations in pigmentation, a phenotype that has been linked to virulence previously (Tsai et al, 1998;1999). However, we observed that swollen conidia of the DmedA mutant, which do not contain pigment, were even less virulent in Galleria than were quiescent conidia (data not shown).…”
Section: Discussionmentioning
confidence: 70%
“…It is also possible, although less likely, that other MedA-dependent factors are responsible for mediating the reduced virulence of this strain. Conidia of the DmedA mutant displayed alterations in pigmentation, a phenotype that has been linked to virulence previously (Tsai et al, 1998;1999). However, we observed that swollen conidia of the DmedA mutant, which do not contain pigment, were even less virulent in Galleria than were quiescent conidia (data not shown).…”
Section: Discussionmentioning
confidence: 70%
“…Recently, we and others have shown that conidia, lacking pigmentation due to a mutated pksP gene (polyketide synthase involved in pigment biosynthesis), were less resistant to attack by monocytes in vitro , and showed reduced virulence in a murine animal model (Jahn et al ., 1997;Tsai et al ., 1998;Brakhage et al , 1999). To investigate whether the presence of a functional pksP gene affects intracellular processing of ingested conidia by macrophages, both A. fumigatus wild-type and pksP mutant conidia were analysed with respect to phagolysosome formation and intracellular kill in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Some environmentally regulated genes a¡ecting growth have been described in the genus Aspergillus [17,18]. Recent work has suggested that the alb1 gene of A. fumigatus, which is involved in melanin biosynthesis, has a role in the modulation of virulence [19]. We believe that further characterization of strain phsA1 will clear up the role of this temperature-and pH-regulated response gene that is also involved in production of a melanin-like pigment in A. nidulans.…”
Section: Resultsmentioning
confidence: 85%